AVALIAÇÃO DAS PROPRIEDADES NANOTOXICOLÓGICAS DO ÓLEO DO GÊNERO Astrocaryum NAS FORMAS LIVRE E NANOEMULSIONADA IN VIVO - Pintos, Francieli Guedes (2019)
Alternative treatments with the use of natural agents are highlighted. In addition, intelligent delivery systems such as nanostructured systems are also growing. Therefore the proposal of this work was to develop a nanoemulsion containing Tucumã oil, to characterize it and to analyze its pharmacological activity in vitro and in vivo. Considering the beneficial properties of Tucumã, the objective was to use it in the form of nanoemulsion, in order to protect the photosensitivity presented by the oil, as well as to develop a more efficient system for the delivery of those favorable activities provided by its compounds. First, a preformulation study of the nanoemulsion containing Tucuman oil was carried out, together with the analysis of different concentrations of these formulations. After these results demonstrated a safety in the concentration of 500 μg / mL in emulsions with the lowest oil content, we decided to work only with the formulation that comprised the smallest quantity. After preparation of the formulations they were characterized by proposing a shelf life. The following parameters were analyzed: refractive index, mean particle diameter, polydispersity index, zeta potential, pH and microscopy on days 0, 7, 15, 30, 60 and 90 days at different temperatures: cooling, climatic chamber and room temperature. Through the results of this step it is possible to highlight the refrigeration condition as the best form of storage, showing stability in the mean particle size of 169.1 nm, polydispersion index of 0.11 zeta potential of - 18.3 mV and pH of 4 , 6 mV at the end of 90 days. In the in vivo assays we have highlighted alternative models such as fish to examine possible toxic effects in experiments with molecules and nanoparticles in different routes of administration as performed in this study. In this way it was possible to demonstrate a toxic synergism between surfactants used, causing different lesions and behavior changes in the animals, as well as possible aggregations formed from these nanostructures. At the same time, the concentrations of TSO 100, NE 100 and 300 and NEBr 300 were those that were shown to be more toxic, leading to the totality of death at the end of the 7 days of oral treatment. It is clear that toxicity tests of nanoformulations are extremely important for clarification in the biological system of living beings and the environment.